Signalling functions of alpha-tocopherol in smooth muscle cells - (:unkn) unknown (VERLAG HANS HUBER, 1997)
alpha-Tocopherol but not beta-tocopherol, activates protein phosphatase 2A, decreases protein kinase C activity and attenuates smooth muscle cell proliferation at physiological concentrations. beta-Tocopherol prevents the effects of alpha-tocopherol. Inhibition of protein kinase C alpha but not of the other isoforms, by the inhibitor Go6976 prevents the effect of alpha-tocopherol. Protein kinase C alpha, immunoprecipitated from alpha-tocopherol treated cells, is less phosphorylated and inactive. It is proposed that the specific activation of protein phosphatase 2A by alpha-tocopherol results in dephosphorylation and inactivation of protein kinase C alpha. Finally, this cascade of events leads to smooth muscle cell proliferation inhibition.
Keywords: alpha-tocopherol; vitamin E; protein kinase C; vascular smooth muscle cell; cell proliferation; protein phosphatase; oxidative stress; PROTEIN-KINASE-C; VITAMIN-E CONSUMPTION; CORONARY-DISEASE; CAROTID-ARTERY; PROLIFERATION; ATHEROSCLEROSIS; ANTIOXIDANT; RAT; PHOSPHORYLATION; PATHOGENESIS